School mathematical practices as experiences of identity work: the learning journeys of three students - Röj-Lindberg, Ann-Sofi (NOMAD Nordic Studies in Mathematics Education, 2015)
This paper illuminates, through stories, how three students’ school mathematical practices accumulate over the years into descriptions of identity in relation to school mathematics. The stories are based on semi-structured interviews with students who were successful during lower secondary school from the perspective of their mathematics teachers’ reform objectives and according to formal assessments. There was not, however, parallel successes in their personal identifications with the school mathematical enterprise as a whole. The study shows that, from the perspective of the student taking part in school mathematical practices, a sense of belonging to learning communities considered as legitimate is of uttermost importance.